Plant extracellular vesicles: A novel bioactive nanoparticle for tumor therapy - Tan, Zhao-Lin; Li, Jing-Fei; Luo, Hao-Ming; Liu, Yang-Yang; Jin, Ye (Frontiers in Pharmacology, 2022)
Extracellular vesicles are tiny lipid bilayer-enclosed membrane particles, including apoptotic bodies, micro vesicles, and exosomes. Organisms of all life forms can secrete extracellular vesicles into their surrounding environment, which serve as important communication tools between cells and between cells and the environment, and participate in a variety of physiological processes. According to new evidence, plant extracellular vesicles play an important role in the regulation of transboundary molecules with interacting organisms. In addition to carrying signaling molecules (nucleic acids, proteins, metabolic wastes, etc.) to mediate cellular communication, plant cells External vesicles themselves can also function as functional molecules in the cellular microenvironment across cell boundaries. This review summarizes the application of plant extracellular vesicles in malignant tumors to intervene in the development of cancer cells, target delivery of active ingredients, and serve as potential drug delivery platforms for tumor therapy.